Opening Doors to Using Nonprofit Community-Based Services to Better Cope With Breast Cancer: A Descriptive Interpretive Study of Women's Experience - Barbara Gentil; Susan Usher; Christine Loignon; Dominique Tremblay (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2024)
Introduction: Nonprofit community-based organizations (COs) are expected to complement specialized cancer care and help meet the needs of people living with and beyond cancer. However, nonprofit community organization (CO) services are underused by women living with and beyond breast cancer (WLWB-BC). Objective: The objective of this study is to explore women's experience of using CO services. Methods: The study is designed as a qualitative study using Interpretive Description. Ten WLWB-BC with experience using CO services were recruited for individual interviews. Thematic content analysis of interview data relied on an iterative 3-cycle coding process to identify factors that affect women's activation to use CO support services. Results: Interviews reveal variations in women's recognition of their need for support, in their experience of identifying COs to meet these needs, and in the process of accessing and using CO services. The concept of candidacy emerges as a determinant process in the use of CO services, influenced by the highly contextualized quality of interactions between women, cancer team professionals and COs. Discussion and Conclusion: Integrating CO services requires more productive interactions. Our findings shed light on how WLWB-BC seek response to their needs outside specialized cancer care. An important aspect is how they see themselves as candidates for CO services and how care providers legitimate perceived needs and eligibility. Candidacy and productive interactions create a virtuous circle supporting activated and informed providers which in turn support WLWB-BC activation in self-management and CO service utilization.